Validation of the Norwegian version of MAPPIN'SDM, an observation-based instrument to measure shared decision-making in clinical encounters. Issue 3 (March 2017) - Kienlin, Simone; Kristiansen, Maria; Ofstad, Eirik; Liethmann, Katrin; Geiger, Friedemann; Joranger, Pål; Tveiten, Sidsel; Kasper, Jürgen
Highlights: MAPPIN'SDMnorge proved reliable and accurate at detecting shared decision-making. MAPPIN'SDM adds consideration of both information quality and mutuality of the communication. Divergence between MAPPIN'SDM and OPTION5 indicates the need for a conceptual debate. Abstract: Objective: To validate the Norwegian version of MAPPIN'SDM observer scales with regard to reliability, accuracy and the extent to which the scales include the essentials of the shared decision-making concept. Methods: Three MAPPIN'SDM scales, focusing on the skills of doctor, patient and dyad, were applied to audiovisual records of 35 decision sequences. Inter-rater reliabilities were determined based on kappa coefficients. Sensitivities and specificities were calculated with regard to an expert reference standard. Convergent validities were calculated with the OPTION5 scale. MAPPIN'SDM was qualitatively compared to OPTION5 using Makoul & Clayman's Integrative Model structure. Results: Inter-rater reliabilities were high on average over 11 items in each of three observer scales (MAPPINdoctor  = 0.77, MAPPINpatient  = 0.82, MAPPINdyad  = 0.77). Patient involvement was detected accurately (MAPPINdyad : mean sensitivity/specificity 93/91%). Comparison with OPTION5 showed weak to moderate correlation (Spearman's ρ/p-value: MAPPINdoctor : = 0.44/0.009, MAPPINpatient : 0.38/0.024, MAPPINdyad 0.40/0.016) and little content overlap. Conclusion: MAPPIN'SDMnorge is capable of assessing SDM highly reliably and accurately. Divergence from OPTION5 reflects explicit disagreement regarding the concept's assumptions. Practice implications: MAPPIN'SDMnorge is ready for use in Norway. In-depth debate on the SDM concept's essentials is urgently needed.